2018
DOI: 10.15587/1729-4061.2018.136371
|View full text |Cite
|
Sign up to set email alerts
|

Studying the influence of the intensity of mechanochemical activation on the process of steam conversion of coal

Abstract: Продовжується вивчення процесу конверсiї вугiлля в синтез-газ в умовах аерозольного нанокаталiзу та обґрунтовано очiкуванi переваги майбутньої промислової технологiї. До переваг можна вiднести можливiсть змiнювати швидкiсть реакцiї шляхом впливу на iнтенсивнiсть механохiмiчної активацiї каталiзатору. Дослiдження процесу проводилось в реакторi, де механохiмiчна активацiя здiйснюється шляхом обертання каталiтичної системи. Вплив iнтенсивностi активацiї на хiмiчнi реакцiї в умовах аерозольного нанокаталiзу ранiше… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Peculiarities of the process of coal gasification in conditions of aerosol nanocatalysis are studied in [17]. The study [18] reveals the influence of mechanochemical activation on the rate of release of synthesis gas from coal and the gas composition. Studies [17,18] have shown a possibility of obtaining synthesis gas of a given composition and the use of this gas as a raw material for FTS.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Peculiarities of the process of coal gasification in conditions of aerosol nanocatalysis are studied in [17]. The study [18] reveals the influence of mechanochemical activation on the rate of release of synthesis gas from coal and the gas composition. Studies [17,18] have shown a possibility of obtaining synthesis gas of a given composition and the use of this gas as a raw material for FTS.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The study [18] reveals the influence of mechanochemical activation on the rate of release of synthesis gas from coal and the gas composition. Studies [17,18] have shown a possibility of obtaining synthesis gas of a given composition and the use of this gas as a raw material for FTS. Previous studies of FTS [19] using the MCA catalyst have shown the feasibility of studies on the effect of pressure on the activity and selectivity of Fe-Cu-K catalyst under AnC conditions at a pressure of 0.1-1.2 MPa.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Adsorption is one of the stages of catalysis, so mechanical activation of MA can affect adsorption as a separate process. Studies of processes using coal as a raw material [14,15] have shown that coal can be mechanically activated. This formed the basis of this work, where ash from coal combustion was activated under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical activation of leonardite involves the use of an activating extractant (ZnCl2, H3PO4, NaOH, KOH, etc. ), which is mixed with raw materials under certain extraction conditions and extract humic substances in the form of watersoluble humates [16][17][18][19]. In the case of physical activation, the raw material is activated under the influence of elevated temperatures or mechanical action on the raw material [20,21].…”
mentioning
confidence: 99%